The economy-energy-environment Nexus in IMF’s Top 2 biggest economies: a TY approach - Atta Mills, Ebenezer Fiifi Emire; Zeng, Kailin; Baafi, Mavis Agyapomah (Journal of Business Economics and Management, 2020)
This paper assesses the relationship between carbon emissions, economic growth and, energy consumption, in USA and China from the perspective of Granger causality, in a multivariate framework controlling for financial development, urbanization, and trade openness. Econometric techniques employed include unit root tests, Toda and Yamamoto Granger causality, and generalized impulse response and variance decomposition analysis for the time horizon 1980–2017. Test results indicate that governments of the USA and China cannot implement sturdier strategic energy policies in the long run without inhibiting the growth of the economy because of the bidirectional causative linkage between economic growth and energy use. A causal link does not exist between carbon emissions and financial development for both countries. Nevertheless, in the USA, there exists a unidirectional Granger causality controlling from energy consumption to financial development. In both economies, urbanization Granger causes CO2 emissions and energy use but the reverse does not hold. An upsurge in energy consumption and carbon emissions will lead to a surge in trade openness but not vice versa for China. A noteworthy result is that there is a substantiation of unidirectional causality from energy consumption to carbon emissions in both countries. In the USA, impulse response and variance decomposition analysis disclosed the effect of financial development is projected to have diminutive magnitude whiles in the future, energy use, economic growth, trade openness, and urbanization would influence carbon emissions significantly. The impacts of trade openness and financial development are expected to be of little importance in China. The general findings implied that urbanization, economic growth, and energy consumption influenced CO2 emissions significantly in the USA and China. Understanding these similar and contrasting situations is essential to reaching a global agreement on climate change affecting IMF’s top 2 biggest economies. First published online 07 November 2019